IMPLEMENTASI KONEKSI JARINGAN INTERNET BERBASIS WI-FI DAN PELATIHAN PADA GURU-GURU SMK N 1 SIBOLGA - Hakim, Arief Rahman; Simanjuntak, Marthin Yohannes; Tampubolon, Laswandi; Harefa, Sepakat Jaya (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2022)
Internet technology keeps on developing and touching various aspects of human daily life. Starting from the very simple utilization of internet, such as the use of email for communication purposes, browsing varied information, up to the relatively advanced one, such as designing and developing homepage or the use of internet for shopping purposes (e-shopping). Some initiatives, either individually or in collaboration, to utilize internet for learning has been conducted by some Secondary Schools that have equipped themselves with computers and other necessary equipment needed, both hardware and software. Socialization for introducing the utilization of computer and internet can be begun from the more equipped Secondary Schools in the cities of provincial and district levels in line with the availability of internet infrastructure connectivity.